Borderline Tuberculoid Leprosy following BCG Vaccination. A Case Report - Stoner, Gerald L.; Belehu, Ayele; Nsibambi, John; Warndorff, Jan (INTERNAL IONAL JOURNAL OF LEPROSY, 1981)
We describe a case of leprosy in a child following vaccination with Bacillus Calmette-Guerin (BCG). Our finding confirms observations made more than 20 years ago (2 . 5 ' 9 ) and illustrates a concept of the leprosy spectrum which has important implications for the design and interpretation of a leprosy vaccine trial
Keywords: BCG Vaccination; Leprosy; Tuberculoid